A Morphometric Study to Find Correlations among Various Dimensions of Proximal End of Humerus of Telugu Population - Sinchal Datta (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Long bones from skeletal remains are useful for identification of the deceased, estimation ofstature, determination of sex etc. in case of fracture of proximal humerus, the contra lateral head dimensionsare used as a template for making prosthesis in replacement surgery.Aims and Objectives: To study and compare the morphometric data of proximal end of humerus of Telugupopulation with similar studies of other ethnic populations, and generate regression equations using themeasured parameters.Material and Methods: Study was conducted on 159 unpaired dry humeri (72 right and 87 left) fromthe collection of Department of Anatomy, Mamata Medical College, Khammam, Using slide calliper andOsteometric board.Results: The mean of maximum length of humeri of right/ left side were 309.88 ± 20.07/ 303.97 ± 22.07,the mean of transverse diameter of humeri of head of right/ left were 38.95 ± 3.38/38.21 ± 3.68, the meanof vertical diameter of humeri of right/ left were 42.77 ± 3.86/41.28 ± 3.84,the mean of circumference ofsurgical neck of right/left were 81.18 ± 8.47/79.58 ± 7.30. Circumference of surgical neck had a strongpositive correlation with transverse diameter & vertical diameter of head which was statistically significant( p < 0.001).Conclusion: The morphometric parameters of proximal end of right humeri were found to greater thanthat of the left humeri. The mean humeral length was similar to that found in studies of various Indianpopulations.